Susceptibility of planktonic cultures of Streptococcus mutans to photodynamic therapy with a light-emitting diode - Anna Carolina Borges Pereira a Costa; José Chibebe Junior; Cristiane Aparecida Pereira; Ana Karina da Silva Machado; Milton Beltrame Junior; Juliana Campos Junqueira; Antonio Olavo Cardoso Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2010)
The objective of this study was to evaluate the effect of photodynamic therapy with erythrosine and rose bengal using a light-emitting diode (LED) on planktonic cultures of S. mutans. Ten S. mutans strains, including nine clinical strains and one reference strain (ATCC 35688), were used. Suspensions containing 10(6) cells/mL were prepared for each strain and were tested under different experimental conditions: a) LED irradiation in the presence of rose bengal as a photosensitizer (RB+L+); b) LED irradiation in the presence of erythrosine as a photosensitizer (E+L+); c) LED irradiation only (P-L+); d) treatment with rose bengal only (RB+L-); e) treatment with erythrosine only (E+L-); and f) no LED irradiation or photosensitizer treatment, which served as a control group (P-L-). After treatment, the strains were seeded onto BHI agar for determination of the number of colony-forming units (CFU/mL). The results were submitted to analysis of variance and the Tukey test (p < 0.05). The number of CFU/mL was significantly lower in the groups submitted to photodynamic therapy (RB+L+ and E+L+) compared to control (P-L-), with a reduction of 6.86 log10 in the RB+L+ group and of 5.16 log10 in the E+L+ group. Photodynamic therapy with rose bengal and erythrosine exerted an antimicrobial effect on all S. mutans strains studied.